Comment on Passfield et al: defending the use of oxygen uptake as a criterion measure for training load - Slattery, K. M.; Wallace, L. K.; Coutts, A. J. (International Journal of Sports Physiology and Performance, 2022)
Comment to Passfield et al: validity of the training-load concept (SPONET ID 4078178) We would like to defend the "indefensible." While appreciating the thought-provoking article put forward by Passfield et al,1 we believe they have incorrectly criticized our choice of oxygen uptake (VO2) as a criterion measure to assess the validity of common methods for quantifying training load.2 In our original paper, it was remiss of us not to explicitly justify the use of VO2 as a criterion measure.2 Yet given the well-established validity of VO2 as a measure of the metabolic cost of aerobic exercise, we did not consider it necessary.